Dynamic capabilities in the automotive industry under digitalisation - a quantitative study in the automotive supplier industry. (18th December 2020) - Knobbe, Florian; Proff, Heike
Digitalisation affects companies at all firm levels: it enables digital processes, digital products/services and digital business models and therefore also complete new digital value systems, and leads to long-term discontinuous change, particularly in the capital-intensive automotive industry. Dealing with changes demands the dynamic capabilities of sensing, seizing and reconfiguring operational capabilities and changing business activities. In times of long-term discontinuous changes under digitalisation, different patterns of (more or less discontinuous and comprehensive) activation of dynamic capabilities and their utilisation for changes in operational capabilities and business activities can be determined. A quantitative study at German automotive suppliers shows that companies fall into five distinct patterns of activating and utilising dynamic capabilities under digitalisation and that this results in distinct leverage points in the business activities.